The Olympic Games Effect: How Sports Marketing Builds Strong Brands - DAVIS, John (Institutional Knowledge at Singapore Management University, 2008)
The Olympic Games attracts fans from all over the world with a diverse range of interests, from a passionate love of sports, to fervent nationalism, to the thrill of athletic competition. This book explains and examines why companies vie to be Olympic sponsors and the tangible and intangible returns they reap for their investment. Starting with a brief history of the Olympics, from the Ancient Greeks to now (including interesting parallels between the ancient and modern games), the book then shows why and how the Olympic Games have become one of the worlds most powerful brands, and the resulting impact for companies that are Olympic sponsors. The book also examines why cities, including Beijing in 2008, invest billions in hosting the Games. From tragedy to astounding success, the Olympics have been the source of some of the most important stories of our times. Readers are provided with a clear understanding of the traditions that have shaped this unique event, as well as the risks involved for stakeholders. Throughout, this compelling book offers invaluable lessons for companies considering almost any type of sports sponsorship investment.